The penetration tester's guide to web applications - Borso, Serge (Artech House information security and privacy series., 2019)
"This innovative new resource provides both professionals and aspiring professionals with clear guidance on how to identify and exploit common web application vulnerabilities. The book focuses on offensive security and how to attack web applications. It describes each of the Open Web Application Security Project (OWASP) top ten vulnerabilities, including broken authentication, cross-site scripting and insecure deserialization, and details how to identify and exploit each weakness. Readers learn to bridge the gap between high-risk vulnerabilities and exploiting flaws to get shell access. The book demonstrates how to work in a professional services space to produce quality and thorough testing results by detailing the requirements of providing a best-of-class penetration testing service. It offers insight into the problem of not knowing how to approach a web app pen test and the challenge of integrating a mature pen testing program into an organization. Based on the author's many years of first-hand experience, this book provides examples of how to break into user accounts, how to breach systems, and how to configure and wield penetration testing tools."--Publisher's description